The Benefits to Taxpayers from Increases in Students' Educational Attainment - Carroll, Stephen J. (RAND Corporation, 2009)
Increases in educational attainment benefit the public because more highly educated people tend to pay more in taxes, are less likely to use social support programs, and are less likely to commit crimes. This volume examines the monetary value of these benefits over an individual's lifetime and how they vary with education level.